Peningkatan Pemahaman Siswa tentang Sikap, Etika, dan Komunikasi Kerja Melalui Program Guru Tamu di SMK Harapan Al Washliyah - Syarifah Fadillah Natasha; Yus Epi; Yanti (Jurnal Masyarakat Indonesia (Jumas), 2026)
This community service activity aimed to improve vocational students’ understanding of workplace attitudes, professional ethics, and communication through a guest lecturer program at SMK Harapan Al Washliyah. The activity involved 28 twelfth-grade accounting students and applied lecture, discussion, simulation, pre-test, and post-test methods. Evaluation was conducted using 20 multiple-choice questions and 5 essay questions. The results showed that the average score increased from 65 in the pre-test to 85 in the post-test, representing a 30.77% improvement. These findings indicate that the guest lecturer program effectively enhanced students’ workplace soft skills and professional readiness.